Key Considerations for an Economic and Legal Framework Facilitating Medical Travel - Hinrichs-Krapels, Saba; Bussmann, Sarah; Dobyns, Christopher; Kácha, Ondřej; Ratzmann, Nora; Holm Thorvaldsen, Julie; Ruggeri, Kai (Frontiers in Public Health, 2016)
Medical travel has the capacity to counter increasing costs of healthcare by creating new markets and increased revenue for health services, potentially benefiting local populations, economies and health care systems. This paper is part of a broad, comprehensive project aimed at developing a Global Health Access Policy (GHAP). It presents key issues to consider in terms of ensuring economic viability, sustainability, and limiting risk to the many stakeholders involved in the rapidly expanding industry of medical travel. The noted economic and legal barriers to medical travel are based on a synthesis of themes found in an extensive review of the available literature. Economic considerations when setting up a GHAP include a dynamic approach to pricing that is fair to the local population. Legal considerations include the implementation of international quality standards and the protection of the rights of those travelling as well as those of local populations in recipient countries. By taking into account these opportunities, the GHAP will more adequately address existing gaps in the economic and legal regulation of medical travel.